miR-631 Inhibits Intrahepatic Metastasis of Hepatocellular Carcinoma by Targeting PTPRE - Chen, Bingqing; Liao, Zhibin; Qi, Yongqiang; Zhang, Hongwei; Su, Chen; Liang, Huifang; Zhang, Bixiang; Chen, Xiaoping (Frontiers in Oncology, 2020)
MicroRNAs (miRNAs) have been reported to play critical roles in the pathological development of hepatocellular carcinoma (HCC), one of the most common cancers in the world. Our study aims to explore the expression, function and mechanism of miR-631 in HCC. Our findings are that expression of miR-631 is significantly down-regulated in HCC tissue compared with that in adjacent non-cancerous tissue, and low expression of miR-631 in HCC tissue is associated with cirrhosis, multiple tumors, incomplete tumor encapsulation, poor tumor differentiation, and high TNM stage. Our test results showed that miR-631 could inhibit migration, invasion, epithelial-mesenchymal transition (EMT) and intrahepatic metastasis of HCC. Receptor-type protein tyrosine phosphatase epsilon (PTPRE) as a downstream target of miR-631 could promote migration, invasion and EMT of HCC cells. Besides, the expression of PTPRE had a negative correlation with the expression of miR-631 both in vivo and in vitro, and increasing expression of PTPRE could reverse inhibitory effects of miR-631 in HCC cells. In sum, our study first demonstrated that miR-631 targeted PTPRE to inhibit intrahepatic metastasis in HCC. We gain insights from these findings into the mechanism of miRNAs regulation in HCC metastasis and further introduce a novel therapeutic target for HCC treatment.